Karakterisasi Protease dari Bakteri Aeromonas hydrophila - Ace Baehaki; Tati Nurhayati; Maggy T. Suhartono (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2004)
In the last decade, a concern on protease as medicinal target for overcoming bacterial and viral diseases has been rapidly increased because of the obvios involvement of this enzyme in the molecular of the diseases mechanism. The porpuse of this research was to characterize proteases from fish pathogenic bacteria Aeromonas hydrophila. The bacteria were grown in media containing triptone 1%, NaCl 1% and yeast extract 0,5%. The optimum production time of A. hydrophila was 48 h, the optimum pH was 7,5, the optimum temperature was 50oC. Study on the effect of metals ion and spesific inhibitors indicated that protease from A. hydrophila was serin metaloprotease.Keywords: protease, characterization, pathogenic bacteria